Evaluation of heart rate and pulmonary uptake in dipyridamole myocardial perfusion imaging in patients with suspected coronary artery disease and their relationship with clinical risk factors - Siamak Derakhshan; Bahar Moassesghafari; Khaled Rhmani (Iranian South Medical Journal)
Background: Non-imaging findings in myocardial perfusion imaging (MPI) may be helpful in patients with suspected coronary artery disease (CAD). The aim of this study was to investigate heart rate and pulmonary uptake and their relationship with clinical risk factors in these patients. Materials and Methods: A total of 354 non-smokers (98 men and 256 women) with suspected CAD and no history of lung disease who were referred to Kowsar Nuclear Medicine Center in Sanandaj in 2022 for MPI with dipyridamole were examined. Resting heart rate (RHR), peak heart rate after dipyridamole injection (PHR) and lung-to-heart ratio (LHR) in the stress phase were measured and their relationship with age, gender, BMI, diabetes, hypertension and hyperlipidemia was evaluated in two groups –those with normal and those with abnormal scans. Results: Patients with diabetes or hypertension had a significantly higher RHR compared to the non-diabetes non-hypertension cases. PHR had a significant relationship only with age and gender (P<0.0001). In the multivariate regression analysis, a significant correlation was observed between LHR and abnormal scan (P=0.03) and male gender (P=0.01). Conclusion: Although diabetes and hypertension increased RHR, the only factors affecting PHR were age and gender, so that the lowest heart rate response to dipyridamole was observed in older adults and men. In addition to an abnormal scan, male gender also increased the likelihood of an abnormal LHR.